Analisis Penanaman Budaya Organisasi Melalui AKHLAK Culture Journey Dalam Meningkatkan Motivasi Kerja Pegawai Milenial: Studi Kasus Pada PT Surabaya Industrial Estate Rungkut - Ramalio Fahridho Sakti; Nuruni Ika Kusumawardhani (Politeknik Kampar, 2023)
The purpose of this article is to find out how far corporate culture can increase millennial employee motivation. The organizational cultural values applied by BUMN companies are AKHLAK or an acronym for Amanah, Competent, Harmonis, Loyal, Adaptive, and Collaborative stipulated by the Ministry of BUMN in 2022. Millennial employees are currently the next future leaders of BUMN companies, it is important for company to increase the work motivation of millennial employees for the continuation of the company's existence. The method used in this research is in-depth interviews and observation, and data analysis techniques are data reduction and data verification. The results of the study show that corporate culture can increase millennial employee motivation. This means that if the company culture can be embedded and implemented by millennial employees, then millennial employee motivation will increase. With an organizational culture that has been embedded and implemented by all employees, it will have an impact on a work environment that leads to a positive direction. This positive work environment is an important factor in increasing millennial employee motivation. Good performance will arise from high employee motivation.